Concept of Smart City for Education: A Case Study in Kendari, Southeast Sulawesi - Nur, M N A; Musaruddin, M; ., Bunyamin; Zulkaida, W O (KnE Social Sciences, 2018)
One of the aspects of a smart city is smart education. Presently, several cities have been implementing the concept of smart city to improve the quality of life of the society, including in the field of education. The educational system is currently heading to the collaboration between information technology and communication. Concepts of education are, therefore, required in the implementation of a smart city. The purpose of the research was to come up with smart city concepts in educational sector. There were two aspects playing an important role in the implementation of smart city. The aspects were educational system and educational technology. These concepts allowed the government to create educational programs in accordance with smart city such as (1) the aspect of education system by establishing ICT center in every school that is connected to the education agency, (2) aspect of education technology by creating education information system, e-learning, online new student enrollment, computer base examination, application of smartphone for learning, student monitoring system for parents, smart library, and e-academic record. The research was limited to the primary and junior high schools. The research generated concepts of smart city for education that are acceptable in other cities where smart city has been implemented. Keywords: concept, smart city, education